School climate, victimization, and mental health outcomes among elementary school students in China. (December 2018) - Wang, Cixin; Boyanton, Dengting; Ross, Ana-Sophia M.; Liu, Jia Li; Sullivan, Kathryn; Anh Do, Kieu
Although school climate has been identified as a protective factor for youth development in the United States, few longitudinal studies have examined the relationship between school climate and student outcomes in China. This study explored the relationship between school climate, victimization, covitality, internalizing symptoms, and academic achievement, and whether school climate moderated the relationship between victimization and mental health outcomes using longitudinal data. Survey data were collected from 1150 Chinese 3rd to 6th grade students ( M age = 10.27 years, SD = 1.03 years, 55% boys) from five elementary schools at two time points. Regression results showed that school climate factors, including student-teacher relationships, clear expectations, respect for diversity and fairness of rules, predicted victimization, mental health (both internalizing symptoms and covitality), and academic grades six months later. School climate did not moderate the relationship between victimization and mental health. Our results suggest that it is important to foster positive school climate in order to prevent bullying and promote positive youth development among elementary students in China.